Data processing in interactive training methods on the basis of web technologies - Morozova, O.I. (Реєстрація, зберігання і обробка даних, 2019)
Web-oriented technologies become more used in educational activities due to the integration of comprehensive professional knowledge, abilities and skills using network information technologies of the educational systems. The work proposes the creation of professional orientation support systems on the basis of websites of general secondary education institutions and profile departments. The cognitive and situational simulation shall be the basis of these systems. Combining these two technologies, the new approach to studying the learning material, enabling for processes and phenomena modelling to study the new learning material and the application environment, which is close to the real, as well as to solve the typical professional tasks, is received.